2017
DOI: 10.1590/1983-40632016v4742449
|View full text |Cite
|
Sign up to set email alerts
|

DRIS indices in three phenological stages of the carrot crop

Abstract: Carrot is one of the most consumed vegetables in Brazil, where the cultivars currently grown present a high yield potential and nutritional demand, which require constant adjustments in fertilization programs for the crop. This study aimed at determining reference values and diagnostic indices by using the DRIS method in three phenological stages of the carrot crop (around 40 and 70 days after sowing and at harvest), as well as evaluating the possibility of early diagnosis for nutritional limitations. For dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In perennial and short-cycle fruit trees in Brazil, research in the nursery, development, flowering, and fruit filling phases has been documented for crops such as coconut, oil palm, Conilon coffee, and carrot (Bastos et al, 2017;Medeiros et al, 2015;Partelli et al, 2018;Reis et al, 2017), along with studies in India on pomegranate (Gosavi et al, 2017), on apple in China (Shunfeng et al, 2018), on pineapple in Colombia (López-Montoya et al, 2018), and on apple, peach, persimmon, fig, vine, and mandarin in Japan (Freire et al, 2019). Research has also been found for roots and tubers, including yam in Africa (Dagbenonbakin et al, 2012) and in flowers, mainly roses, in greenhouses in Colombia (Franco-Hermida et al, 2013).…”
Section: B Dynamics Of Mineral Elements According To the Phenological Stagementioning
confidence: 99%
See 1 more Smart Citation
“…In perennial and short-cycle fruit trees in Brazil, research in the nursery, development, flowering, and fruit filling phases has been documented for crops such as coconut, oil palm, Conilon coffee, and carrot (Bastos et al, 2017;Medeiros et al, 2015;Partelli et al, 2018;Reis et al, 2017), along with studies in India on pomegranate (Gosavi et al, 2017), on apple in China (Shunfeng et al, 2018), on pineapple in Colombia (López-Montoya et al, 2018), and on apple, peach, persimmon, fig, vine, and mandarin in Japan (Freire et al, 2019). Research has also been found for roots and tubers, including yam in Africa (Dagbenonbakin et al, 2012) and in flowers, mainly roses, in greenhouses in Colombia (Franco-Hermida et al, 2013).…”
Section: B Dynamics Of Mineral Elements According To the Phenological Stagementioning
confidence: 99%
“…In recent years, this method has been used to update and validate the Critical Levels and Sufficiency Ranges of soils planted with oil palm in Colombia (Herrera, 2015) and beans in Brazil (Partelli et al, 2019). The greatest use is at the level of leaf tissue for oil palm in Colombia (Herrera, 2015), carrot (Reis et al, 2017), orange var Pear (Machado et al, 2013), irrigated beans (Partelli et al, 2014), guava (Souza et al, 2015), and sugarcane (Da Silva et al, 2021) in Brazil, and aonla (Nayak et al, 2011), oil palm (Behera et al, 2016), and mango in India (Naik & Bhatt, 2017).…”
Section: Critical Levels and Sufficiency Rangesmentioning
confidence: 99%
“…Despite being more accumulated in the roots (Dezordi et al 2015), K showed an increase in the leaf content at harvest time. This may be explained by the fact that high yields of carrot crops depend on K levels sufficient to maintain a high leaf content, even though the partition of this nutrient to the roots is greater (Aquino et al 2015, Gonçalves et al 2017. A high leaf K is required to maintain high photosynthesis rates (which are necessary for high yields), as this nutrient regulates the mechanism of stomatal opening and closing.…”
Section: Resultsmentioning
confidence: 99%
“…For N, K, Mg, Mn and Zn, these differences were higher at harvest time. This result suggests that the final stages are most adequate for sampling and foliar diagnosis in carrot crops, because a higher plant growth decreases the possibility of errors related to the nutrient concentration and dilution in dry matter (Maia 2012, Gonçalves et al 2017.…”
Section: Variablementioning
confidence: 98%
See 1 more Smart Citation